2020
DOI: 10.1177/1203475420914622
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Features, Management, and Prevention of Herpes Zoster in Patients Receiving Antitumor Necrosis Factor Therapy: A Clinical Review

Abstract: Tumor necrosis factor (TNF) inhibitors have been used as an excellent therapeutic option in a variety of chronic inflammatory conditions. However, a recognized significant adverse effect of TNF inhibitor therapy is the increased risk of infections. The influence of TNF inhibitors on the course of coexisting or newly developed viral infections has not been extensively investigated. Therefore, we reviewed the recent publications to highlight the incidence, clinical features, management, and prevention of herpes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Nagayama et al reported one case in a patient with rheumatoid arthritis after treatment with infliximab [13] , while Santos-Antunes et al reported a case in an IBD patient being treated with anti-TNF-α therapy (adalimumab) [14] . ECCO guidelines state that before starting any biologic therapy, all patients must be asked about any history of chickenpox or shingles [3,15]. If the history is uncertain or negative, they should be tested for varicella-zoster virus IgG [3,16] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nagayama et al reported one case in a patient with rheumatoid arthritis after treatment with infliximab [13] , while Santos-Antunes et al reported a case in an IBD patient being treated with anti-TNF-α therapy (adalimumab) [14] . ECCO guidelines state that before starting any biologic therapy, all patients must be asked about any history of chickenpox or shingles [3,15]. If the history is uncertain or negative, they should be tested for varicella-zoster virus IgG [3,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, close monitoring is crucial since herpes zoster is relatively common in these patients and there is a potentially poor outcome in those treated with anti-TNF agents [3] . Guidelines have been developed for the treatment and prevention of herpes zoster in many immunocompromised situations, but limited information has been published to date regarding the kind of infections, specifically during treatment with biologics [15] . Varicella-zoster reactivation often has a mild, self-limited course, and does not require discontinuation of immunomodulators or systemic antiviral therapy [16] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations